Acute adverse reactions attributed to allopurinol in hospitalised patients. Issue 3 (June 1981) - McInnes, G T; Lawson, D H; Jick, H
Abstract : Of 29 524 hospitalised medical patients monitored in a drug surveillance programme 1835 (6.2%) received the xanthine oxidase inhibitor allopurinol. After the exclusion of skin reactions adverse effects were attributed to this drug in 33 (1.8%) patients, the most frequent being haematological abnormalities (11 patients, 0.6%) and diarrhoea and drug fever (5 each, 0.3%). Adverse effects were dose-related. Reactions were unrelated to age, weight, reason for therapy, admission blood urea, or albumin concentrations. Acute exacerbation of gout was troublesome in 3 patients (1 in 600 exposed).